Taḥlīlu Uslūbi al Insyā’i wa al Khabari fī Syi’ri al Raṡā’i “Falā Yub’idannaka Allāhu” li al Khansā’i (Dirāsatun Taḥlīliyyatun fī ‘Ilmi al Ma’āni) - Danil, Muhammad; Mahendra, Ahdiyat (Jurusan Bahasa dan Sastra Arab Fakultas Adab dan Humaniora UIN Sulthan Thaha Saifuddin Jambi, 2021)
The purpose of this study is to describe and find out the meaning of (1) the meaning of uslub insya’i and uslub khabari (2) The kinds of uslub insya’i thalabi in the ritsa poem by Al Khansa (3) the sentence of poem containing uslub khabari in the ritsa poem by Al Khansa (4) the purpose of revealing the poem of ritsa by Al Khansa. The methodused in this research is descriptive qualitative. In the rhyme of ritsa poem (falayubidannaka Allah) by Al Khansa, there are 14 kinds of uslub insy’i thalabi including: 1. Amar 2. Istifham 3. Tamnni 4. Annida. While the sentences containing uslub khabari in Al Khansa’s rhyme (falayubidannaka Allah) poem are 34 sentences including: 1. Uslub khabari ibtida’i 2. Uslub khabari thalabi and has one of the following goals: 1. For faidatul khabar and 2. Lazimul faidah and has a context meaning purpose including: 1. Izhar dha’fi 2. Izhar tahassur. As for the purpose of the disclosure of poetry ritsa by Al Khansa including 1. Al-madah 2. Al-hamasah.